A case report of pulmonary hepatoid adenocarcinoma: promoting standardized diagnosis and treatment of the rare disease - Xu, Kun; Gao, Jin; Feng, Lili; Fang, Ying; Tang, Xiuliang (Frontiers in Immunology, 2023)
Objective: To investigate the clinical features, pathological characteristics, immunophenotype, differential diagnosis and prognosis of pulmonary hepatoid adenocarcinoma using a clinical case and literature report. Methods: We analyzed the clinical presentation, histological pattern and immunohistochemistry of a case of primary hepatoid adenocarcinoma of the lung in April 2022. We also reviewed literature on hepatoid adenocarcinoma of the lung from PubMed database. Results: The patient was a 65-year-old male with smoking history, who was admitted to hospital with an enlarged axillary lymph node. The mass was round, hard, and grayish-white and grayish-yellow in color. Microscopically, it presented hepatocellular carcinoma-like and adenocarcinoma differentiation features, with abundant blood sinuses visible in the interstitium. Immunohistochemistry showed that the tumor cells were positive for hepatocyte markers, including AFP, TTF-1, CK7 and villin, and negative for CK5/6, CD56, GATA3, CEA and vimentin. Conclusion: Pulmonary hepatoid adenocarcinoma is a rare epithelial malignancy of primary origin in the lung with poor prognosis. Establishing the diagnosis relies mainly on the detection of hepatocellular structural morphology resembling hepatocellular carcinoma, and on clinicopathological and immunohistochemical testing to exclude diseases such as hepatocellular carcinoma. Combination treatment, mainly surgery, can prolong the survival of early-stage cases of the disease, whereas radiotherapy is mostly used for intermediate and advanced cases. Individualized treatment with molecular-targeted drugs and immunotherapy has shown different therapeutic effects for different patients. Further research is needed to better understand this rare clinical condition for the development and optimization of treatment strategies.